Dynamic performance of Indonesian public companies: An analysis of financial decision behavior - Muchtar, D; Albra, W; Arifai, M; Ahmar, AS; Fauzias Mat Nor (Taylor & Francis As, 2024)
Indexed by WOS/ Scopus